Medioevo, fonti, editoria. La Deputazione di storia patria per le Venezie (1873-1900) - Orlando, Ermanno (Reti Medievali E-Book, 2016)
The book analyzes the first three decades of the life and activities of the Deputazione di storia patria per le Venezie, with special focus on its editorial policies. The study also aims to investigate the content and methodologies of medieval studies in Venice and Veneto; the cultural orientation of the Deputazione; the organization's role in establishing liaisons between the central body and the individual municipal traditions; the relationship with the research institutions of the Kingdom of Italy, and the significance of studies on the Middle Ages and medieval sources in the formation of a national identity; and, lastly, the Society's commitment to promoting and popularizing the local sources and its efforts to define a method for publishing them.